2014
DOI: 10.1007/s40477-014-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Our ultrasonographic experience in the management of symptomatic hydronephrosis during pregnancy

Abstract: Introduction The aim of the present study was to document the role of ultrasound in the diagnosis and management of symptomatic hydronephrosis during pregnancy. Methods In this study, we reviewed 36 consecutive cases of pregnant women whose pregnancy was complicated by symptomatic hydronephrosis. In all patients, management was initially conservative (analgesics and fluids) after hospitalization. The following criteria were used to indicate double-J stent placement under US guidance rather than a conservative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In the present study, hydroureteronephrosis was observed in 47.5% of the study subjects on the right side and 30% of the study subjects on the left side while Oyinloye et alin their study reported that hydroureteronephrosis of pregnancy was observed in 93.4% of the study subjects in the right side and 84.4% of the study subjects in the left side [22]. Dell'atti et al in their study reported that hydroureteronephrosis of pregnancy was observed in 61% of the study subjects on the right side and in 39% of the study subjects on the left side which is consistent with the findings of our study [23]. Hydroureteronephrosis is more pronounced on the right side.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, hydroureteronephrosis was observed in 47.5% of the study subjects on the right side and 30% of the study subjects on the left side while Oyinloye et alin their study reported that hydroureteronephrosis of pregnancy was observed in 93.4% of the study subjects in the right side and 84.4% of the study subjects in the left side [22]. Dell'atti et al in their study reported that hydroureteronephrosis of pregnancy was observed in 61% of the study subjects on the right side and in 39% of the study subjects on the left side which is consistent with the findings of our study [23]. Hydroureteronephrosis is more pronounced on the right side.…”
Section: Discussionsupporting
confidence: 91%
“…A renal pelvis AP diameter of >20 mm in pregnant women is considered as progressive hydronephrosis. In some previous studies, surgical treatment was recommended for pregnant women with severe or progressive hydronephrosis [15, 19]. In some other studies, cut-off values were determined for renal pelvis AP diameter in treatment selection and its use as a predictive parameter in treatment selection was emphasized.…”
Section: Commentmentioning
confidence: 99%
“…And a few weeks after birth completely disappeared (15,18,20). The first-line imaging test to diagnose maternal hydronephrosis is ultrasonography (US) (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Because US is a non-invasive and ionizing radiation-free imaging technique (21). In addition, maternal nephrosonography findings during pregnancy were quantitatively and qualitatively documented years ago (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation